Reflections and guidelines for the study of vernacular landscapes - Frank, Bruno Jose Rodrigues [UNESP]; Yamaki, Humberto Tetsuya (Univ Fed Goias, Inst Estudos Socio-ambientais, 2021)
Coined by J.B Jackson in the 1970s, the concept of Vernacular Landscape was used to appreciate certain landscapes in the United States that were considered banal or common, seeking to interpret and value it. Since then, this concept has been worked within the studies of Cultural Landscape. Despite the wide range of possible interpretations, the Vernacular Landscape as a concept does not have the systematic theoretical and methodological it deserves. The aim of this article is to fill this gap by conceptualizing it and look for the particularities that differentiate it from other categories of Cultural Landscape. Therefore, we defined certain guidelines and parameters for its interpretation, followed by the most relevant research approaches. The article also brings, as an example, the of an Invernada (similar to paddocks in the northern hemisphere), where some of the guidelines discussed are applied in the text.
Keywords: Vernacular Landscape; Cultural Landscape; Methodolog; Theory and practice